2017
DOI: 10.2147/ndt.s118076
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between subtypes and symptoms of ADHD, insomnia, and nightmares in connection with quality of life in children

Abstract: ObjectivesThis study examined the links between sleep disorders and subtypes of attention deficit-hyperactivity disorder (ADHD-inattention, ADHD-combined, ADHD-hyperactive/impulsive) in childhood. We set up a hypothetical model linking different symptoms of both disorders to construct the underlying and shared pathways. By examining a sample of children with ADHD we firstly tested parts of the model.MethodsA total of 72 children with symptoms of ADHD (aged 6–13 years; 79.2% boys) were diagnosed according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…School-age children. Quality of life scores were reduced in children with insomnia and ADHD compared with healthy controls 100. Adolescents.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…School-age children. Quality of life scores were reduced in children with insomnia and ADHD compared with healthy controls 100. Adolescents.…”
Section: Resultsmentioning
confidence: 89%
“…Parental reports described longer sleep onset delay,97,99 shorter sleep duration, and more restless sleep in children with ADHD compared with healthy controls 97. Children with ADHD hyperactive/impulsive subtype scored higher on measures of insomnia compared with individuals with an inattentive type,100 and no differences in insomnia scores between children with ADHD and healthy controls were found in another study 99. Adolescents.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, other studies did not find these associations ( 38 , 59 ). Some studies also reported significant associations between DD frequency and attention deficit hyperactivity disorder (ADHD) ( 60 ) as well as with ADHD subtypes ( 61 , 62 ), and one prospective study found that parent-rated DDs at 10–19 years of age predicted symptoms of inattention and direct/indirect aggression at 18–32 years of age ( 55 ).…”
Section: Introductionmentioning
confidence: 99%
“…[8] Because of serious consequences of ADHD for the patients and their families such as inattention, hyperactivity, and impulsivity, the patients face with impaired learning abilities at school, sleep disorder, social isolation, and thus with reduced quality of life for the patient and his/her family members. [9] Over the last century, several studies have focused the association between AD and ADHD. Unfortunately, we did not have any perspective on this relationship in our country.…”
Section: Introductionmentioning
confidence: 99%